Hubungan Karakteristik Dengan Tingkat Kepatuhan Minum Obat Pasien Diabetes Mellitus Tipe II Di Puskesmas Tiban Baru Kota Batam - Suhaera Suhaera; Suci Fitriani Sammulia; Arie Voniekartika; Nahrul Hasan (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Diabetes mellitus is a frequently encountered degenerative disease. Indonesia, being one of the most populous countries, experiences a notable increase in the global prevalence of diabetes mellitus. Type 2 diabetes mellitus constitutes the most prevalent form, with approximately 90-95% of diabetics falling into this category. Notably, patient compliance in Indonesia falls short of meeting the recommended glycemia target. The root cause of this non-compliance is linked to a lack of understanding among individuals with diabetes mellitus regarding the purpose of therapy, leading to a lack of awareness about potential complications. This research aims to explore the connection between patient characteristics and adherence to medication in Type 2 diabetes mellitus patients at the Tiban Baru Health Center in Batam City. Employing a descriptive correlation approach with a prospective cross-sectional research design, the study utilized purposive sampling, including 92 patients meeting the inclusion criteria. Data collection involved the administration of a compliance questionnaire (MMAS). The study's conclusion reveals a significant association between job characteristics and medication adherence in Type 2 diabetes mellitus patients, evidenced by a p-value of 0.046. Conversely, factors such as gender, age, education, duration of suffering, and comorbidities were not found to be correlated with medication adherence (p-value > 0.05). It is anticipated that healthcare professionals at the Tiban Baru Health Center will impart accurate information to patients, enhancing their awareness of the potential complications associated with diabetes mellitus.